Comparative Studies on the Hepatoprotective Effect of White and Coloured Rice Bran Oil against Acetaminophen-Induced Oxidative Stress in Mice through Antioxidant- and Xenobiotic-Metabolizing Systems - Phannasorn, Warunyoo (Oxid Med Cell Longev, 2021)
Rice bran oil (RBO) comprises various nutrients and phytochemicals which exhibit several health benefits. There are no studies regarding the functional effects of different colours of RBO. This study was aimed to compare the constituents and antioxidant activities of white rice bran oil (WRBO) and coloured rice bran oil (CRBO). Each RBO showed similar free fatty acid profiles. However, greater amounts of vitamin E, phytosterols, carotenoids, and chlorophylls were found in CRBO, which had lower γ-oryzanol content than WRBO. Oxidative stress was induced in male mice by an overdose of acetaminophen (APAP) at 300 mg/kg body weight. The mice were then fed with RBO at the equivalent dose to 100 mg/kg body weight of γ-oryzanol three hours later and sacrificed six hours after APAP treatment. The administration of 100 mg γ-oryzanol equivalent in CRBO ameliorated APAP-induced hepatotoxicity in mice more strongly than 100 mg γ-oryzanol equivalent in WRBO, as evidenced by the significant reduction of serum ALT, hepatocellular necrosis, and hepatic lipid peroxidation. CRBO could improve xenobiotic-metabolizing and antioxidant enzyme activities, including glutathione S-transferase, superoxide dismutase, glutathione peroxidase, and glutathione reductase, and also increase mRNA expression of various antioxidant-responsive genes. Vitamin E, phytosterols, carotenoids, and chlorophyll might be the protective compounds in CRBO that alleviate APAP-induced hepatotoxicity through the interruption of APAP metabolism and the activation of antioxidant systems at both transcriptional and enzymatic levels. These findings might provide a protective role of CRBO on oxidative stress associated with several degenerative diseases.